Solanum Whitefly, Pepper Whitefly (Suggested Common Names) Aleurotrachelus trachoides Back (Insecta: Hemiptera: Aleyrodidae: Aleyrodinae) - Vivek Kumar; Antonio Francis; Muhammad Z. Ahmed; Catharine M. Mannion; Ian Stocks; Eric Rohrig; Cindy L. McKenzie; Lance S. Osborne (EDIS, 2020)
Includes: Introduction - Synonymy - Distribution - Description and Biology - Hosts - Damage - Management - Selected References